Effect of FYM, Phosphorus and PSB on Growth, Yield and Quality of Greengram [Vigna radiata (L.) Wilckzek] on Loamy Sand - Rekha, Karnavat; R. P., Pavaya; Chaudhary, Neha; Patel, Sweta (International Journal of Bio-resource and Stress Management, 2018)
A field experiment was conducted during kharif, 2014 on phosphorus management in greengram to study the effectof two FYM levels viz., 0 t FYM ha-1 and 10 t FYM ha-1 and seven treatments of phosphorus viz., Only PSB, 20 kg P2O5 ha-1, 20 kg P2O5 ha-1+PSB, 30 kg P2O5 ha-1, 30 kg P2O5 ha-1+PSB, 40 kg P2O5 ha-1 and 40 kg P2O5 ha-1+PSB on growth, yield attributes and yield and economics of greengram [Vigna radiata (L.) Wilckzek]. Application of 10 t FYM ha-1 gave maximum values of all the growth and yield attributes of greengram. This application registered 7.2 and 7.3% higher seed and stover yield as compared to control respectively. Significantly higher value of growth parameters, yield attributes, yield and quality parameters were recorded with 10 t FYM ha-1 application as compare to no FYM application. Phosphorus application 40 kg P2O5 ha-1+PSB were significantly increased on growth and yield attributes (plant height, branches plant-1, root nodules plant-1, fresh and dry weight of root nodules, pod length, pods plant-1, 1000 grain weight), seed and stover yield compared to PSB only. Application of 40 kg P2O5 ha-1+PSB resulted significant increase in all these atrributes over PSB only. Absolute control (only PSB) produced significantly poor performance of these attributes than rest treatments.